Assessment of interest in drugs based on the active ingredient bisoprolol using the Google Trends search engine - Pyvovarov, Oleksandr (The Ukrainian Scientific Medical Youth Journal, 2026)
to assess the level of interest in medicines based on the active ingredient bisoprolol in Ukraine and the world using the technology of the Google Trends search resource. To assess the general trends of interest in the medicine сoncor with the active ingredient bisoprolol using the Google Trends web tool, search activity in English and separately only for its active ingredient bisoprolol in the world since 2004 was analyzed. Google Trends is a technology used to study the trends and patterns of search queries in Google and allows scientists to obtain quantitative and qualitative indicators of user queries in Google, to determine current trends in different countries of the world in different time dimensions for analysis. The study is devoted to assessing the interest in the popular medicine Concor based on the active ingredient bisoprolol using modern search technologies Google Trends. Solving the problem of assessing the level of interest in the new drug Concor in the world by analyzing search queries in English on Google showed that this topic is significant for research. The evaluation of indicators showed that since 2004 there has been a steady increase in the search activity of Google users for drugs based on the active ingredient bisoprolol. The countries with the highest level of interest during the search were highlighted. Google Trends technology allows scientists to obtain quantitative and qualitative indicators of Google users' queries and determine current trends in different countries of the world for analysis. Search activity on Google for the drug сoncor and the active ingredient bisoprolol is high in the world. The existence of a relationship between the data of the WHO 2025 report on the prevalence and awareness of hypertension and search activity for antihypertensive drugs in different countries of the world was noted, therefore, further use of the Google Trends search engine to assess the level of interest in new drugs for patients with arterial hypertension in Ukraine and the world may be promising.